Water management for sustainable prosperity: a model that inspired Anna Hazare - Pangare, Ganesh; Lokur, Vasudha (New Delhi, 2009)
Water wars are a cruel reality today. This book look at Vilasroas Salunkhe's successful 'pani cpanchayat' water model for useful replication across India. Anna Hazare was also inspired by the same and introduced it in his village.
Keywords: Pani panchayat (Maharashtra)